Effect of life purpose program on the wellness of juvenile delinquents with a history of alcohol use detained at the juvenile detention center: A quasi-experimental study - Balthip, Karnsunaphat; Phoomchaiya, Sirimas; Nudla, Palida; Suwanruangsri, Sarana; Sathirapanya, Chutarat; Buathong, Napakkawat (Belitung Nursing Journal, 2025)
Background: Juvenile delinquency with a history of alcohol use is a growing concern with a significant impact on their holistic well-being. Life purpose (LP) has been recognized as essential for enhancing adolescent wellness. LP should therefore be useful in addressing juvenile delinquency. Objective: This quasi-experimental study investigated the effect of the life purpose program on the wellness of juvenile delinquents with a history of alcohol use in Southern Thailand. Methods: Sixty-seven delinquents, aged 15 to 19, from the Juvenile Detention Center were randomly assigned to either the intervention group (n = 35) or the control group (n = 32). The intervention group engaged in an eight-week purpose program, whereas the control group continued with routine care. Wellness outcomes were measured using the Wellness Scale (WS) and analyzed through multilevel mixed-effects modeling. Results: At baseline, there were no significant differences in wellness scores between the control and intervention groups. Following the intervention, wellness scores at weeks 16 and 24 were significantly higher in the intervention group compared to the control group (t = -6.101, p<0.001; t = -2.856, p = 0.008, respectively). The multilevel mixed effects model confirmed a significant improvement in wellness scores over time in the intervention group (β = 3.746; 95% CI = 0.22–7.27; p = 0.037). Conclusion: The program was successful in improving wellness among juvenile delinquents with a history of alcohol use and shows promise for broader application. It should be implemented by nurses and other professionals as part of efforts to promote a sense of life purpose in similar populations. However, further research is needed to evaluate its long-term impact and sustainability. Integrating the life purpose program into existing rehabilitation processes may enhance the overall well-being of juvenile detainees. Trial Registry Number: Thai Clinical Trials Registry (TCTR20241217002)